THE EFFECT OF WARM COMPRESSES ON REDUCING LABOR PAIN IN 1 ACTIVE PHASE - HUMAIRA, HILDA; PRASETYANINGSIH; ZALMADANI, HENDRO (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2024)
Labor pain is one of the most prominent aspects and often causes discomfort to the mother during the labor process, especially during the first stage of the active phase. This study aims to determine the effect of warm compresses on reducing pain intensity in mothers giving birth at TPMB Hj. Yetti Latif S. ST. The research method used was quasi- experimental with a pre-test and post-test design without a control group. A total of 15 mothers giving birth during the first active phase were selected as respondents using an accidental sampling technique. Pain intensity was measured using a numerical scale before and after the warm compress intervention. The results of the study showed a significant reduction in pain intensity after administering a warm compress, with an average reduction in pain of 3 points on a numerical scale (p<0.05). The results of the univariate analysis found that 87% of women in labor experienced a reduction in labor pain in the first stage of the active phase from severe to moderate after applying a warm compress and 13% experienced a reduction from very severe to severe pain. Bivariate analysis found a p-value (p<0.05), meaning that there was a significant relationship between the effect of warm compresses and a decrease in the intensity of labor pain in the first active phase (p=0.001). The conclusion of this research is that warm compresses are effective in reducing the intensity of labor pain in the active phase of the first stage and can be one of the non-pharmacological interventions recommended in birthing facilities. The implementation of this method is expected to increase maternal comfort during labor and minimize the need for more invasive medical interventions.